2013
DOI: 10.1111/ctr.12100
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous pancreas kidney transplants in diabetic patients with end‐stage renal disease: the 20‐yr experience

Abstract: Despite the differences between groups by BMI, age of onset of insulin use, and age at transplant, there was a difference in patient but not graft survival within the 20 yr follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…When data were stratified by diabetes mellitus type, there was no observed difference in patient or pancreatic graft survival [ 39 ]. Long-term (20-year) data from the Light et al [ 38 ▪▪ ] series also suggest similar patient and graft survival regardless of diabetes type after risk stratification. In another single-center review of SPK transplants from Europe published in 2013, authors identified 21 patients of 216 who were transplanted for a diagnosis of T2DM [ 46 ].…”
Section: Type 2 Diabetesmentioning
confidence: 88%
See 1 more Smart Citation
“…When data were stratified by diabetes mellitus type, there was no observed difference in patient or pancreatic graft survival [ 39 ]. Long-term (20-year) data from the Light et al [ 38 ▪▪ ] series also suggest similar patient and graft survival regardless of diabetes type after risk stratification. In another single-center review of SPK transplants from Europe published in 2013, authors identified 21 patients of 216 who were transplanted for a diagnosis of T2DM [ 46 ].…”
Section: Type 2 Diabetesmentioning
confidence: 88%
“…Complicating its clinical utility, fasting C-peptide levels may be falsely high in patients with CKD and/or gastroparesis [ 37 ]. Additionally, C-peptide is not always positive in the T2DM patients, further confounding the diagnosis [ 38 ▪▪ , 39 ]. There is a clear need for more precise, multiparameter or genetic categorizations of T1DM, T2DM, and/or other forms of diabetes before transplantation.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…Recently, two studies support the option of SPK for type 2 diabetic patients. Long-term data suggest similar patient and graft survival regardless of diabetes type after risk stratification [ 39 ]. In another single-center review of 216 SPK transplants from Europe, 21 of them had a diagnosis of type 2 diabetes [ 40 ].…”
Section: Results Of Transplantation In Type 2diabetic Patientsmentioning
confidence: 99%
“…The C peptide cut-off is another source of debate, since it does not fully correlate with diabetes type 38,39 , and C peptide levels do not predict outcome 40,41 ; prompting some to propose raising the cut-off to 10 ng/ml to include more T2DM patients 34 .…”
Section: Pancreas Transplantationmentioning
confidence: 99%